E-Ticket Application as Supporting Technology During COVID-19 Pandemic in Baluran National Park - Kristanto, Sepyan Purnama; Yusuf, Dianni; Hakim, Lutfi; Rifqi, Mochamad Misbahur (INTEK: Jurnal Penelitian, 2021)
The COVID-19 outbreak has a major impact, especially on tourism. Closure of tourist attractions must be enforced to prevent the spread of the virus. People are required to maintain a safe distance and avoid crowds (physical distancing). Some policies and guidelines are created to adapt to the new normal era to drive and stabilize the people's economy during this pandemic. Tourist attractions start operating with government guidelines, including limiting the number of visitors and implementing supporting technology to prevent queues of visitors when purchasing entrance tickets. This study develops a web-based system to facilitate ordering tickets through a web-based system, uploading proof of transfer, and obtaining e-tickets to be shown to ticket officers. Extreme Programming model was used. The e-ticket system has been tested at Baluran National Park using the Blackbox method, showing that the system has the functionality to meet user needs.